Analysis of ACE2 Gene-Encoded Proteins Across Mammalian Species - Cao, Ying; Sun, Yeping; Tian, Xiaodong; Bai, Zhihua; Gong, Yue; Qi, Jianxun; Liu, Di; Liu, Wenjun; Li, Jing (Frontiers in Veterinary Science, 2020)
Human beings are currently experiencing a serious public health event. New coronavirus disease 2019 (COVID-19), caused by the novel severe acute respiratory syndrome coronavirus (SARS-CoV-2), has infected about 3 million people worldwide and killed more than 200,000, most being the elderly or people with potential chronic diseases or in immunosuppressive states. According to big data analysis, there are many proteins homologous to or interacting with the angiotensin-converting enzyme 2 (ACE2), which, therefore, may not be the only receptor for the novel coronavirus; other receptors may also exist in host cells of different species. These potential receptors may also play an important role in the infection process of the novel coronavirus. The current study aimed to discover such key proteins or receptors, and analyze the susceptibility of different animals to the novel coronavirus, in order to reveal the transmission of the virus in cross-species infection. We analyzed the proteins coded by the ACE2 gene in different mammalian species and predicted their correlation and homology with the human ACE2 receptor. The major finding of our predictive analysis suggested ACE2 gene-encoded proteins to be highly homologous across mammals. Based on their high homology, their possibility of binding the spike-protein of SARS-CoV-2 is quite high and may be potential susceptible hosts, such as Felis catus, Bos taurus, Rattus norvegicus et al., special monitoring is particularly required for livestock that are in close contact with humans. Our results might provide ideas for the prevention and control of the novel coronavirus pneumonia.